Foot Reanimation Using Double Nerve Transfer to Deep Peroneal Nerve: A Novel Technique for Treatment of Neurologic Foot Drop. (August 2021) - El-Taher, Mohamed; Sallam, Asser; Saleh, Mohamed; Metwally, Ahmed
Background: Our primary objective was to assess the efficacy of a new technique for foot reanimation in patients with neurologic foot drop using double nerve transfer from the tibial to the deep peroneal nerve. Our secondary objective was to document the technical nuances of our technique. Methods: Thirty-one patients with common peroneal nerve injury between October 2015 and March 2019 were prospectively enrolled in the study. Patients underwent a transfer of the tibial nerve branches to flexor digitorum longus and lateral head of gastrocnemius to the deep peroneal nerve. Motor recovery, range of ankle dorsiflexion, pain, leg girth, and complications were examined as outcome measures. The modified Medical Research Council (MRC) scale was adopted to assess the motor power recovery. All patients were followed up for a minimum of 1 year. Results: Motor recovery of M3 or M4 grade of tibialis anterior, extensor hallucis longus, and extensor digitorum longus was achieved in 15 of 31, 13 of 31, and 12 of 31 patients, respectively. Those patients could discontinue use of orthosis. Most patients with high-energy traumas or knee-level injuries failed to recover antigravity function. Only 2 patients reported weak postoperative toe plantarflexion. Our patients achieved significant improvement of the pain perception and range of active ankle motion at the final follow-up. Conclusion: The double nerve transfer technique represented a feasible and safe surgical option. It has been shown to improve function in some patients with neurologic foot drop resulting from a less than 12-month injury of the deep peroneal nerve. Level of Evidence: Level IV, therapeutic.